Functional macromolecular complexes - Yamamoto, Kimihisa (Coordination chemistry discovery series, 2024)
Functional macromolecular complexes are classified as distinctive functional material groups in the fields of chemistry and materials science. This book provides a comprehensive introduction to the synthesis and applications of functional macromolecular complexes with a focus on Japanese chemists who are leading this field. Translated from the original Japanese title, it gives an overview of the synthesis, structures, functions, and applications of functional macromolecular complexes in an easily understandable manner.Useful for students who are interested in functional materials, as well as researchers and young scientists new to coordination chemistry in academic and industry settings, the book will help to generate new scientific and technological advances for the future